A Concepção de Vontade Geral mediante as perspectivas do pensamento de Rousseau e Hegel - Pereira, Bruno Limana (2010)
The troubles that Hegel s philosophy imposed for the grasp of politic brought a restatement which combine elements that transcend the sheer assessing of being only a theory grounded in liberals doctrines, aggregating a shape of search to intermediate the aspect of juridical abstract law, that is, one that in which the citizens get into like bears of right in the private field, reaching on the acknowledge of subject like moral agent, to be able achieve the deed through particular circumstances not covered by juridical law and, lastly, sketching the structure of social and public institutions faced the components of society that culminated in the state. It s in this walk down to up, that is since the abstraction of private right until the necessary superstructure of the state that we attempt to search into a concept subjacent at the circuit of the institutions mainly political, a key-concept that was inherited of Rousseau: is the concept of the General Will. This way a revision upon the premises of the Social Contract must have a right to due confrontation with Hegel s view that take on other perspective and adopt a different reading in comparison to his French antecessor. The formulation of topic, therefore, will be in this research revisited and reflected with an eye to grasp the difference in both the philosophers which will implicate the retaking of notions such as freedom, contract, liberalism and, of course, the own concept of state, leading us at conclusion that want to enlighten the meaning of the expressions inside the context of the Philosophy of Right, seemingless obscure and few deepened.